2023
DOI: 10.3390/su152115600
|View full text |Cite
|
Sign up to set email alerts
|

Does Digital Transformation Promote Green and Low-Carbon Synergistic Development in Enterprises? A Dynamic Analysis Based on the Perspective of Chinese Listed Enterprises in the Heavy Pollution Industry

Sen Wang,
Jinye Li

Abstract: Digital transformation has become essential in promoting and upgrading enterprise elements and reshaping the market’s competitive landscape. However, whether digital transformation can further promote green and low-carbon synergistic development is still being determined. Using data from 2008 to 2014 matched between A-share listed enterprises in China’s heavily polluting industries and China’s industrial enterprise pollution emission database (robustness tests were used city panel data from 2013 to 2019 to ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Du and Qu [22] observed that the investment and application of digital technologies enable enterprises to foster the creation of sustainable development value. Additionally, research has indicated that corporate digital transformation can facilitate green technology innovation [23], enhance supply chain performance [24], generate synergistic effects in carbon reduction [25], and hold significant implications for the development of a low-carbon economy.…”
Section: Introductionmentioning
confidence: 99%
“…Du and Qu [22] observed that the investment and application of digital technologies enable enterprises to foster the creation of sustainable development value. Additionally, research has indicated that corporate digital transformation can facilitate green technology innovation [23], enhance supply chain performance [24], generate synergistic effects in carbon reduction [25], and hold significant implications for the development of a low-carbon economy.…”
Section: Introductionmentioning
confidence: 99%